2013
DOI: 10.1021/jp402507v
|View full text |Cite
|
Sign up to set email alerts
|

Photoelectron Angular Distributions of Pyridinide: A Benchmark Application of the Mixed s–p Model to a Truly Polyatomic Anion

Abstract: We report a photoelectron imaging study of the pyridinide anion, C5H4N(-), obtained by deprotonation of pyridine at the C4 position. The photoelectron angular distributions are used to test the theoretical formalism for photodetachment from mixed-character s-p states, demonstrating its first application to a truly polyatomic system. The mixed s-p model describes the initial state of the anion in terms of a superposition of one s orbital and one p orbital centered on the deprotonated carbon. Using the model par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
40
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(45 citation statements)
references
References 36 publications
5
40
0
Order By: Relevance
“…The X̃states, on the other hand, have localized s-p hybrid Dyson orbitals, which allows for partial l = 0 detachment and retained intensity at small eKE. 41 Calculated photodetachment cross sections, shown in Figure 3, are consistent with this threshold behavior for the X̃and Ãstates of both species.…”
supporting
confidence: 69%
“…The X̃states, on the other hand, have localized s-p hybrid Dyson orbitals, which allows for partial l = 0 detachment and retained intensity at small eKE. 41 Calculated photodetachment cross sections, shown in Figure 3, are consistent with this threshold behavior for the X̃and Ãstates of both species.…”
supporting
confidence: 69%
“…2. The Dyson orbitals for the e X states, on the other hand, have localized s-p hybrid character, enabling partial l = 0 detachment, and significant intensity at small eKE (40). Photodetachment cross sections calculated as a function of eKE are shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Modeling the Photoelectron Angular Distributions. The PADs for cyclic deprotonated anions can be described with good accuracy and conceptual insight using the mixed s−p model, 9,29,30 which is a partial case of the general mixing theory presented recently. 31 The mixed s−p model approximates the MO of the parent anion, from which the observed photoelectrons are (nominally) emitted, with a model function ψ sp , defined as a superposition of one s and one p-type functions, with the (1 − γ p ) 1/2 and (γ p ) 1/2 amplitudes, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…32,35 Our own past work has shown that the choice of cos δ 2,0 = 0.95 instead of 1 results in only minor changes in the mixed s−p model predictions. 9 In view of these findings and acknowledging that the phase shift exists but is small, we will set cos δ 2,0 = 0.95 throughout the analysis. This choice is somewhat arbitrary but does not affect the overall trends discussed.…”
Section: Discussionmentioning
confidence: 99%